Ландшафтно-геоекологічне значення міграції важких металів у системі "грунт-рослина" - Бортнік, Л.О.; Черваньов, О.І. (Культура народов Причерноморья, 2005)
Вивчено процес переносу важких металів у системі грунт-рослина у якості елементів живлення й забруднювачів, з урахуванням фізіологічного впливу їх на рослини у залежності від фенофази вегетації. Складено камерну модель переносу важких металів і визначені малі параметри процесу. Для верифікації моделі використано власні емпіричні дані. Изучен процесс миграции тяжелых металлов в системе почва-растение с учетом физиологического эффекта их воздействия на растения в качестве элементов питания и загрязнителей, в зависимости от фенофазы вегетации. Предложена камерная модель переноса тяжелых металлов и определены малые параметры процесса. Для верификации процесса использованы собственные эмпирические данные. Migration of the selected heavy metal pollutants in soil-plant system and their effect on plants is studied for different phenophases of the vegetation period of plants. Chamber model is constructed to describe transport of pollutants through the soil-plant chain. The model is solved to the leading order in the small parameters that are identified by analyzing the obtained empirical data. The model covers the cases where the selected heavy metals play the role of either pollutants or mineral nutrition of plants. The obtained theoretical results are verified by making a comparison with the empirical data, obtained independently.